Computational Discovery of Novel Chalcogenide Perovskites YbMX3 (M = Zr, Hf; X = S, Se) for Optoelectronics - Qingyu Li; Helong Wu; Weiguo Li; Jiming Zhang; Rongjian Sa (Molecules)
Chalcogenide perovskites have shown great potential for photovoltaic applications. Most researchers have begun to pay close attention to the crystal synthesis, phase stability, and optoelectronic properties of chalcogenide perovskites AMX3 (A = Ca, Sr, Ba; M = Ti, Zr, Hf, Sn; X = S, Se). At present, the A-site metal cations are mainly limited to alkaline earth metal cations in the literature. The replacement of the alkaline earth metal cations by Yb2+ is proposed as an alternative for chalcogenide perovskites. In this study, the phase stability, and mechanical, electronic, optical, and photovoltaic properties of novel chalcogenides YbMX3 (M = Zr, Hf; X = S, Se) are theoretically evaluated in detail for the first time. It is mentioned that YbZrS3 and YbHfS3 are marginally thermodynamically stable while YbZrSe3 and YbHfSe3 exhibit superior phase stability against decomposition. Good mechanical and dynamical stability of these chalcogenide perovskites are verified, and they are all ductile materials. The accurate electronic structure calculations suggest that the predicted direct bandgap of YbMSe3 (M = Zr, Hf) is within 1.3–1.7 eV. Additionally, the small effective mass and low exciton binding energy of YbMSe3 (M = Zr, Hf) are favorable for their photovoltaic applications. However, YbZrS3 and YbHfS3 show larger direct band gaps with a change from 1.92 to 2.27 eV. The optical and photovoltaic properties of these compounds are thoroughly studied. In accordance with their band gaps, YbZrSe3 and YbHfSe3 are discovered to exhibit high visible-light absorption coefficients. The maximum conversion efficiency analysis shows that YbMSe3 (M = Zr, Hf) can achieve an excellent efficiency, especially for YbZrSe3, whose efficiency can reach ~32% in a film thickness of 1 μm. Overall, our study uncovers that YbZrSe3 is an ideal stable photovoltaic material with a high efficiency comparable to those of lead-based halide perovskites.